Nitrosative Stress-Induced Disruption of Baroreflex Neural Circuits in a Rat Model of Hepatic Encephalopathy: A DTI Study - Tsai, Ching-Yi (Sci Rep, 2017)
The onset of hepatic encephalopathy (HE) in liver failure is associated with high mortality; the underlying mechanism is undecided. Here we report that in an acute liver failure model employing intraperitoneal administration of thioacetamide in Sprague-Dawley rats, diffusion weighted imaging revealed a progressive reduction in apparent diffusion coefficient in the brain stem. Diffusion tensor imaging further showed that the connectivity between nucleus tractus solitarii (NTS), the terminal site of baroreceptor afferents in brain stem and rostral ventrolateral medulla (RVLM), the origin of sympathetic innervation of blood vessels, was progressively disrupted until its disappearance, coincidental with the irreversible cessation of baroreflex-mediated sympathetic vasomotor tone signifying clinically the occurrence of brain death. In addition, superoxide, nitric oxide, peroxynitrite and ammonia levels in the NTS or RVLM were elevated, alongside swelling of astroctytes. A scavenger of peroxynitrite, but not an antioxidant, delivered intracisternally reversed all these events. We conclude that nitrosative stress because of augmented peroxynitrite related to accumulation of ammonia and swelling of astrocytes in the NTS or RVLM, leading to cytotoxic edema in the brain stem and severance of the NTS-RVLM connectivity, underpins the defunct baroreflex-mediated sympathetic vasomotor tone that accounts for the high mortality associated with HE.